Improving the Patient’s Safety and Quality of Life with Minimizing Hospital Readmission Post Endoscopic Renal Stone Surgery RIRS - Aous Abed Al-Jaleel Khaleel (Diyala Journal of Medicine, 2025)
Background: Technology advancement of retrograde intrarenal surgery is important in elevating its efficiency and safety for renal and upper ureter stone management. Objectives: To evaluate the efficiency and safety of retrograde intrarenal surgery with a flexible and navigable ureteral access sheath in the management of renal and upper ureter stones. Patients and Methods: It was a clinical prospective follow-up study carried out in Life Private Hospital in Kalar city, Kurdistan region, Iraq, over the period of one year, from 1st of January to 31st of December 2024. A sample of one hundred patients underwent retrograde intrarenal surgery with a flexible and navigable sheath. The diagnosis of stones was done by a researcher and a Radiologist or referral from other physicians from different specialties through abdominal ultrasound and computerized tomography scan. Results: The preoperative clinical co-morbidities were present in 37% of patients, commonly diabetes mellitus (18%), hypertension (12%), and heart disease (7%). The preoperative urine culture was positive in 17% of patients. Preoperative stent was done for 31% of patients, commonly for non-compatible ureter (20%), pain (9%), and sepsis (2%). No stone fragments or sepsis were reported postoperatively among the patients studied. Conclusion: The retrograde intrarenal surgery using flexible and navigable ureteral access sheath is an effective and safe surgical procedure in the management of kidney and upper ureter stones. Keywords: Kidney stone, Retrograde intrarenal surgery, Flexible and navigable sheath.